Flexural Behavior Of GFRP-Reinforced Concrete Beam Strengthened With Cast-In-Place Textile In Tension Zone With Minimum Reinforcement Ratio - Alaa Aziz Muneam; Layth A.Al-Jaberi; Hesham A.Numan (Genius Journals, 2023)
TRM is usually composed of continuous textile fabrics embedded into a compendious matrix. This application has gained serious attention within the civil engineering scientific field due to several futures. These features are represented by good mechanical properties like the high strength of textiles, a considerable level of young’s modulus, and a good bond between textiles and mortar. The present experimental program investigates the flexural behavior of the GFRP bars reinforced concrete beams that include TRM layers at the top and bottom of its section. The section is of 200 mm in total height, 120 mm in width, and 1100 mm in center-tocenter span. The specimens map comprises five specimens, two of these are referential (GFRP and steel reinforcement) and the others are TRM beams with two, four, and five textile layers respectively. The third, fourth, and fifth specimens are compared with the two referential specimens. These specimens are reinforced with a minimum reinforcement ratio and includes TRM at the section bottom (tension). The experimental results exhibited that using two, four, and six TRM layers in the beams section bottom increases the first cracking load, service load, and rapture load respectively. In addition, the differentiation between GFRP and steel bars stress-strain curve caused a connective difference in flexural behavior. When the TRM layers are located in the section bottom (tension zone), the service load increased from 23.76% to 76.03% by increasing the number of layers to six while the stiffness increased from 14.66% to 27.19%. meanwhile, increasing TRM bottom layers to six decreased the ductility from 6.06 % to 18.69 %. Finally, Using TRM bottom layers can change the mode of failure from tension to tension-compression
Keywords: GFRP; Reinforced Concrete; Cast-In-Place; Textile